The Effects of Brand Hypocrisy on Consumer Evaluations and Behaviors: Moderating Role of Nutrition Consciousness - Erol, Fuat (Organizations and Markets in Emerging Economies, 2023)
Many individuals accuse brands of hypocrisy for lacking transparency and sincerity, which could harm the brands’ image and lead to negative evaluations. Accusations of hypocrisy can also result in negative behavioral outcomes, such as brand distance and negative word of mouth (nWOM). This is particularly true for food brands, as it depends on individuals’ nutrition consciousness. Therefore, this study aims to explore the serial mediating effect of brand image and brand evaluations of the effect of the brand (mission) hypocrisy on both brand distance and nWOM, and the moderating role of nutrition consciousness on these indirect effects. Data was collected from 463 Turkish participants, and moderated serial mediation analyses were performed to test the research hypotheses. As a result, brand hypocrisy has a direct effect on brand evaluations, brand distance, and nWOM; nutrition consciousness has a moderating role on the effect of brand hypocrisy on brand image, and finally, brand image and brand evaluations serially mediate the effect of brand hypocrisy on brand distance and nWOM, where nutrition consciousness moderates both indirect effects. Thus, the current study theoretically and empirically advances the limited literature on brand hypocrisy and nutrition consciousness, and focuses on the assessment process of individuals and its behavioral outcomes.